CASE-FATALITY AND MORTALITY FROM ACUTE MYOCARDIAL INFARCTION IN THE ELDERLY POPULATION IN THE CITY OF NIS - Biljana Kocić (Acta Medica Medianae, 2007)
Acute myocardial infarction (AMI) is an important cause of mortality in the elderly. The aim of the paper was to determine the frequency of mortality due to AMI in the elderly population (≥65 years of age). The data about all hospitalized patients with AMI were analized. Data were taken from the Population-based Register for AMI of the City of Nis. The total number of registered cases was 1917, 1065 (55,6%) of which in men and 852 (45,4%) in women. Among the elderly men, there were 214 (20,1%) cases of fatal AMI and 237 (27,8%) cases of fatal AMI among the elderly women. The difference found was statistically significant (c2=36,5140 and p<0,001). The average 30-day case-fatality for AMI was 34,4% in men and 45,5% in women. The differance determined was statistically significant (c2=5,62580 and p<0,05). In regard to the age, the highest 30-day case-fatality both in men and women was in the age group 75-79 years (37,8%:38%) and the lowest 30-day case-fatality was in the group of patients older than 90 year (1,4%:3%). The standardized prehospital and hospital mortality rates for men were much higher than for women. The standardized mortality rate in men ranged from 3,7 to 102/100 000. The same mortality rate in women ranged from 8,6 to 60,7/100 000. There were more elderly women with fatal AMI than men. Both non-standardized and standardized mortality rates from AMI have shown continuous increase in the elderly, especially in men. The average of 30-day case-fatality has been consistently reported as being higher among women. There has been a decrease of 30-day case-fatality among men from 2004. The 30-day case-fatality among women showed an increase in 2006. Both non-standardized and standardized prehospital and hospital mortality rates both in men and women have increased.